-30x+42=6(x+9)

Simple and best practice solution for -30x+42=6(x+9) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -30x+42=6(x+9) equation:


Simplifying
-30x + 42 = 6(x + 9)

Reorder the terms:
42 + -30x = 6(x + 9)

Reorder the terms:
42 + -30x = 6(9 + x)
42 + -30x = (9 * 6 + x * 6)
42 + -30x = (54 + 6x)

Solving
42 + -30x = 54 + 6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-6x' to each side of the equation.
42 + -30x + -6x = 54 + 6x + -6x

Combine like terms: -30x + -6x = -36x
42 + -36x = 54 + 6x + -6x

Combine like terms: 6x + -6x = 0
42 + -36x = 54 + 0
42 + -36x = 54

Add '-42' to each side of the equation.
42 + -42 + -36x = 54 + -42

Combine like terms: 42 + -42 = 0
0 + -36x = 54 + -42
-36x = 54 + -42

Combine like terms: 54 + -42 = 12
-36x = 12

Divide each side by '-36'.
x = -0.3333333333

Simplifying
x = -0.3333333333

See similar equations:

| 180-x+12=2x | | -1/3M=12 | | 180-2x=X+12 | | 42=5z+12 | | -3(x+8)=x+4 | | 4n+8-2n=2n-5 | | Y=-xsquared+12x-5 | | (x-10)^2/3=-6 | | 8x+35=30x+24 | | -3/4b27 | | c/8=27 | | Y=4xsqrt(x) | | x^2+y^2-7x-5y+40=0 | | 4(x-7)+5x-2=-3 | | 6(x+8)=48 | | 7/8x=-2/3 | | 4x-25=5x | | 4d+6-6d=120 | | a+54=69 | | 1/2y=6x-5/9 | | -2y^2-7y+39=0 | | 25+6x-7=36 | | Y+4y+10=5(y+2) | | -15+6x=-24+6x+9 | | 12x=y-5 | | Cd-4=5cford | | 4(15+12)+5(8)= | | 8c+5-5c+7=36 | | 5(2-x)=2(4+3x) | | 12-1x=3x | | 3x+-4+2x=0 | | Ln(x^3)-3=0 |

Equations solver categories